2019
DOI: 10.1002/ajmg.a.61183
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of rare coding variants in genes implicated in risk of human cleft lip with or without cleft palate

Abstract: Cleft lip with/without cleft palate (CLP) is a common craniofacial malformation with complex etiologies, reflecting both genetic and environmental factors. Most of the suspected genetic risk for CLP has yet to be identified. To further classify risk loci and estimate the contribution of rare variants, we sequenced the exons in 49 candidate genes in 323 CLP cases and 211 nonmalformed controls. Our findings indicated that rare, protein‐altering variants displayed markedly higher burdens in CLP cases at relevant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…The findings supported the role of CLPTM1(3), NECTIN1 (19), OFC1 (22), SPRY2 (23), THADA (24), SHTN1 (54), NOGGIN (27), TPM1 (30), GREM1 (31), PAX7 (34), SHH (36), SIX3 (37), BRIP1(BACH1) (38), BRCA1 (40), MAFB (26), FOXE1 (42), AXIN2 (43), SNAI1 (46), BRCA2 (40), GLI2 (48), GRHL3 (49), COL21A1 (50), WNT5A (51), TOX3 (52), and SOX9 (52) in the development of a CL ± P malformative phenotype. The findings also revealed that GAD1 (28), ARHGAP29 (39), and DVL2 (43) were regulatory proteins essential for proper development of the face.…”
Section: Genes Associated With Orofacial Closure Defectssupporting
confidence: 76%
“…The findings supported the role of CLPTM1(3), NECTIN1 (19), OFC1 (22), SPRY2 (23), THADA (24), SHTN1 (54), NOGGIN (27), TPM1 (30), GREM1 (31), PAX7 (34), SHH (36), SIX3 (37), BRIP1(BACH1) (38), BRCA1 (40), MAFB (26), FOXE1 (42), AXIN2 (43), SNAI1 (46), BRCA2 (40), GLI2 (48), GRHL3 (49), COL21A1 (50), WNT5A (51), TOX3 (52), and SOX9 (52) in the development of a CL ± P malformative phenotype. The findings also revealed that GAD1 (28), ARHGAP29 (39), and DVL2 (43) were regulatory proteins essential for proper development of the face.…”
Section: Genes Associated With Orofacial Closure Defectssupporting
confidence: 76%
“… 91 )) of the WNT-signaling pathway. Defects or expression disruptions of wnt9b , tpbg , sfrp5 and pou2f1 genes lead to deficiency in the WNT signal pathway, and bilateral craniofacial asymmetry and skull malformation in vertebrates 92 , 93 , including zebrafish 94 . Our analyses also revealed substantial changes in physicochemical properties and three-dimensional structure of these WNT components in RFP (for example, T212P and P428S cause polarity changes of amino acids in pou2f1; T169K caused charge changes in tpbg; K236R caused protein structure changes in sfrp5) (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…We also analyzed a set of 13 previously identified nsCL/P candidate genes with: (1) a significant enrichment of low-frequency variants (four genes), 60 (2) an autosomal-dominant inheritance pattern in multigenerational families (four genes), 61 or (3) an enrichment of rare coding variants (five genes). 62 Of these, 12 genes were present in the analysis set. Two of these 12 genes approached test-wide significance: PRTG (p = 8.44 × 10 − 5 ) and CTNND1 (p = 2.17 × 10 − 5 ; Table S8 ).…”
Section: Resultsmentioning
confidence: 99%